Regression Analysis In Determining The Influence Of Relative Humidity Towards Workers' Performance - Ahmad Rasdan, Ismail (2010)
Ergonomics has traditionally been used to improve the workers' performance by discovering the factors that contribute to their performance. Many organizations are forced to consider effects of environmental factors towards their workersâ performance in terms of safety and efficiency. The objective of this study is to determine the effects of humidity on the operatorsâ productivity and performance in the Malaysian automotive industry. One automotive components assembly factory was chosen as the sources of subjects of the study. The subjects were the workers in the assembly section of the factory. The examined parameters were the relative humidity (%) of the surrounding workstation area. Two sets of representative data consisting of the relative humidity (%) and production rate were collected during the study. The production rate data were collected through observations and survey questionnaires, while the relative humidity (%) was measured using thermal comfort multi-station (TCM) equipment.Linear regression analysis was performed to obtain the relationship between the effects of relative humidity (%) on worker productivity and performance. The linear regression analysis further revealed a linear model with a positive slope between relative humidity (%) and worker productivity for the assembly section involved. The obtained relationship was Y = 2.79 X â 46.1